Corona Virus Infection among Healthcare Workers in a COVID Dedicated Tertiary Care Hospital in Dhaka, Bangladesh - Yasmin, Rubina; Parveen, Rahnuma; Azad, Nazim Al; Deb, Sudip Ranjan; Paul, Nandita; Haque, Md Manjurul; Haque, Md Ahsanul; Azad, Shehreen (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Health care workers (HCWs) are at high risk of acquiring infections during this ongoing COVID-19 outbreak. This study was aimed at determining the prevalence of SARS-CoV-2 infection, the socio demographic and clinical profile and the possible risk factors for infection among the HCWs at Mugda Medical College Hospital (MuMCH). Method: This retrospective observational study was done among the HCWs of MuMCH from 19 April, 2020 to 15 May, 2020. The SARS-CoV-2 positive 37 HCWs were interviewed over telephone by a structured questionnaire and the obtained data were analyzed by using descriptive statistics. Result: Out of total 343 HCWs, total 37(10.79%) cases were detected COVID-19 positive. Out of them, 13(35.14%) were male and 24 (64.86%) were female. The median age was 36 years. Among the infected HCWs, 26 (70.27%) did not have any pre-existing comorbidities. Bronchial asthma (13.51%) and HTN (13.51%) were the most prevalent comorbidities. Around 43.24% (16) had no definite symptoms for COVID- 19. Among the 21(56.76%) symptomatic cases, 15(40.54%) had mild and 6(16.22%) had moderate symptoms. The most common symptoms were cough (16, 43.24%), fever (11, 29.73%), sore throat (7, 18.92%) and fatigue/malaise (7, 18.92%). All had completely recovered uneventfully although 22(59.46%) got admitted to hospital. Only 12(32.43%) were involved in aerosol generating procedure. Total 26 cases (70.27%) used appropriate PPE during their duty. Although only 4(10.81%) got adequate training on PPE use, 33(89.19%) of them had adequate knowledge on that. About 15(40.54%) were reusing PPEs. Most of them (33, 89.20%) were not taking any chemoprophylaxis; all were following traditional preventive measures. Among the HCWs, 26(70.27%) were not satisfied with the infection prevention and control (IPC) measures taken by the hospital authority. All of them presumed that, their occupational exposure was the possible source of COVID-19 infection. Conclusion: More than 1 in 10 HCWs at MuMCH was infected with SARS-CoV-2 while working at the hospital. They represented the younger age group, had fewer comorbidities. Nurses were the most affected category. All experienced uneventful recovery and most of them were not satisfied with the IPC measures taken by the hospital authority. Further studies are required to identify the level of risk of infection, possible risk factors and outcomes and to improve the IPC measures of the hospital. J Bangladesh Coll Phys Surg 2020; 38(0): 43-49